The Roles of Neutrophils Linking Periodontitis and Atherosclerotic Cardiovascular Diseases - Irwandi, Rizky A.; Chiesa, Scott T.; Hajishengallis, George; Papayannopoulos, Venizelos; Deanfield, John E.; D’Aiuto, Francesco (Frontiers in Immunology, 2022)
Inflammation plays a crucial role in the onset and development of atherosclerosis. Periodontitis is a common chronic disease linked to other chronic inflammatory diseases such as atherosclerotic cardiovascular diseases (ASCVD). The mechanistic pathways underlying this association are yet to be fully understood. This critical review aimed at discussing the role of neutrophils in mediating the relationship between periodontitis and ASCVD. Systemic inflammation triggered by periodontitis could lead to adaptations in hematopoietic stem and progenitor cells (HSPCs) resulting in trained granulopoiesis in the bone marrow, thereby increasing the production of neutrophils and driving the hyper-responsiveness of these abundant innate-immune cells. These alterations may contribute to the onset, progression, and complication of atherosclerosis. Despite the emerging evidence suggesting that the treatment of periodontitis improves surrogate markers of cardiovascular disease, the resolution of periodontitis may not necessarily reverse neutrophil hyper-responsiveness since the hyper-inflammatory re-programming of granulopoiesis can persist long after the inflammatory inducers are removed. Novel and targeted approaches to manipulate neutrophil numbers and functions are warranted within the context of the treatment of periodontitis also to mitigate its potential impact on ASCVD.